Option Pricing Bounds in Discrete Time - PERRAKIS, STYLIANOS; RYAN, PETER J. (Journal of Finance, 1984)
ABSTRACT Upper and lower bounds are derived for call options traded at discrete intervals. These bounds are independent of assumptions on the stock price distribution other than a restriction satisfied by the stock being “non‐negative beta.” The development of the bounds relies on the single‐price law and arbitrage arguments. Both single‐period and multiperiod results are produced, and put option bounds follow by extension. The bounds exist as equilibrium values given a consensus on stock price distribution; they are also valid for empirical studies, being adjustable for dividends and commissions.